Aproximación sociolingüística al doblado de clítico de objeto directo en Lambayeque, Perú - Fernández-Doig, Fabiola (2022)
In this research, we analyze the accusative clitic doubling in Spanish Lambayeque. We understood accusative clitic doubling as the presence of the clitic of the direct object in co-occurrence with the nominal phrase of the direct object in postverbal position. The analysis is carried out in four cities of Lambayeque: Chiclayo, Eten, Ferreñafe and Mochumí. The four cities studied were chosen according to the level of contact with Quechua, economic activities, and greater centrality in education and services. The analysis was conducted in 72 interviews. We investigate the statistical significance of four linguistic factors: animacy, definiteness, and concordance (of gender and number) in the occurrence of the accusative double. In addition, the social factors of age, gender, and city of origin were studied. The results show that the accusative clitic doubling in this dialect variety is sensitive to the animacy, definiteness, and agreement between the determining phrase (FD) and the corresponding clitic. We found the possibility of proposing a hierarchy of significance among the studied factors.